Power to health reporters: health literacy as a tool to avoid pressures from news sources - Lopes, Felisbela (2021)
ABSTRACT - The second biggest Legionnaires’ disease outbreak worldwide occurred in Portugal in 2014. It was classified by the WHO as a “great public health emergency,” and it was subject to a unique media coverage in Portugal. The media coverage of this outbreak lasted for 2 weeks, which is not very common in similar cases, and it was characterized by the control of information by official sources. These were put together in a joint task force that disseminated all information. Nonetheless, they did not generate a hegemonic discourse which is usually characteristic of power elites. That happened mostly due to the promotion of health and risk literacy. Through infographics, descriptive maps, and questions and answers, the media were able to generate an alternative discourse to that of official sources. That was the basis of a unique media coverage.